New drugs with antiprotozoal activity from marine algae: a review - Torres, Fábio A.e.; Passalacqua, Thais G.; Velásquez, Angela M.a.; Souza, Rodrigo A. De; Colepicolo, Pio; Graminha, Márcia A.s. (Sociedade Brasileira de Farmacognosia, 2014)
The use of indigenous or remote popular knowledge to identify new drugs against diseases or infections is a well-known approach in medicine. The inhabitants of coastal regions are known to prepare algae extracts for the treatment of disorders and ailments such as wounds, fever and stomach aches, as for the prevention of arrhythmia. Recent trends in drug research from natural sources have indicated that marine algae are a promising source of novel biochemically active compounds, especially with antiprotozoal activity. Algae survive in a competitive environment and, therefore, developed defense strategies that have resulted in a significant level of chemical structural diversity in various metabolic pathways. The exploration of these organisms for pharmaceutical and medical purposes has provided important chemical candidates for the discovery of new agents against neglected tropical diseases, stimulating the use of sophisticated physical techniques. This current review describes the main substances biosynthesized by benthic marine algae with activity against Leishmania spp., Trypanosoma cruzi and Trypanosoma brucei; the causative agents of leishmaniasis, Chagas disease and African trypanosomiasis, respectively. Emphasis is given to secondary metabolites and crude extracts prepared from marine algae.
Keywords: Leishmaniasis; African trypanosomiasis; Chagas disease; Natural products; Algae; Drug discovery